The AML1/ETO target gene LAT2 interferes with differentiation of normal hematopoietic precursor cells - Essig, Aitomi (2013)
The adaptor protein linker activator of T-cells 2 (LAT2) is a known AML1/ETO target gene whose function during normal hematopoiesis is unknown. We addressed the role of LAT2 during erythroid and myeloid differentiation of normal human CD34+ hematopoietic cells. LAT2 is expressed at low levels in CD34+ cells and upregulated during cytokine-induced myeloid and erythroid differentiation. Forced LAT2 expression leads to a delay of erythroid and myeloid differentiation keeping CD34+ cells in a more immature state, whereas LAT2 knockdown accelerates differentiation. It is tempting to speculate that by affecting the differentiation capacity of normal hematopoietic progenitors, LAT2 may contribute to the pathogenesis of AML.